Perbedaan Motivasi Belajar Santri yang Berasal dari Keluarga Utuh dan Broken Home di Pondok Pesantren - Ainatus Sholihah; Musbikhin Musbikhin; Nashihin Nashihin (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2021)
Motivation and learning are two things that influence each other. Learning is a change in behavior that is relatively permanent and potentially occurs as a result of practice or reinforcement based on goals, to achieve certain goals. While motivation can be said as the overall driving force of a person that causes learning activities, which ensures the continuity of learning activities and which gives rise to direction in learning activities.This research is a qualitative research that is field research or field research, namely research with data obtained from field activities. In this case the researchers collected and analyzed data from interviews, observations, and documentation in the Pondok Pesantren Sunan Drajat Paciran Lamongan, East Java.The results of the research conducted are 1). The difference in learning motivation between students with intact families and broken home families is very clear, based on the results of interviews, students with broken home families look more enthusiastic in learning than students who come from intact families, 2). There are several factors that influence students' motivation to learn, including: the condition of the students' family, the role of a teacher, and environmental conditions.